2014
DOI: 10.1128/jcm.02378-13
|View full text |Cite
|
Sign up to set email alerts
|

Discordance across Several Methods for Drug Susceptibility Testing of Drug-Resistant Mycobacterium tuberculosis Isolates in a Single Laboratory

Abstract: bGiven the increases in drug-resistant tuberculosis, laboratory capacities for drug susceptibility testing are being scaled up worldwide. A laboratory must decide among several endorsed methodologies. We evaluated 87 Mycobacterium tuberculosis isolates for concordance of susceptibility results across six methods: the L-J proportion method, MGIT 960 SIRE AST, Gene/Xpert MTB/ RIF, GenoType MTBDRplus line probe assay, MycoTB MIC plate, and a laboratory-developed mycobacteriophage quantitative PCR (qPCR)-based met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
58
2
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(64 citation statements)
references
References 8 publications
(6 reference statements)
3
58
2
1
Order By: Relevance
“…Unexpectedly, we obtained a significantly higher correlation between MGIT and MycoTB with EMB (0.79) compared to the previously published value of 0.30 [43]. Generally, the presence of mutations in the embB 296–497 codon region increases the resistance of the strain to EMB to varying degrees, which might be lower than the plasma drug level of 5 μg/ml [44].…”
Section: Discussioncontrasting
confidence: 48%
“…Unexpectedly, we obtained a significantly higher correlation between MGIT and MycoTB with EMB (0.79) compared to the previously published value of 0.30 [43]. Generally, the presence of mutations in the embB 296–497 codon region increases the resistance of the strain to EMB to varying degrees, which might be lower than the plasma drug level of 5 μg/ml [44].…”
Section: Discussioncontrasting
confidence: 48%
“…It has been reported that the results of the Bactec 460 method and AgarPM were discordant (54,55). It was reported that false susceptibility to EMB is of little consequence in settings of susceptible M. tuberculosis isolates (55). Thus, the effect of different drug concentrations on the evaluation of molecular detection of EMB resistance was analyzed.…”
Section: Discussionmentioning
confidence: 99%
“…One study reported that there were a number of ofloxacin-susceptible strains by conventional methods but resistant by MYCOTB and genotypic methods ( gyrA mutant) [3]. Another study conducted by Sayera et al showed that DST of streptomycin worked well with MYCOTB but less well for the conventional phenotypic methods[4] . …”
Section: Introductionmentioning
confidence: 99%